2018
DOI: 10.1111/1759-7714.12613
|View full text |Cite
|
Sign up to set email alerts
|

ALK‐rearrangement in non‐small‐cell lung cancer (NSCLC)

Abstract: The ALK gene encodes a transmembrane tyrosine kinase receptor. ALK is physiologically expressed in the nervous system during embryogenesis, but its expression decreases postnatally. ALK first emerged in the field of oncology in 1994 when it was identified to fuse to NPM1 in anaplastic large‐cell lymphoma. Since then, ALK has been associated with other types of cancers, including non‐small‐cell lung cancer (NSCLC). More than 19 different ALK fusion partners have been discovered in NSCLC, including EML4, KIF5B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
147
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(171 citation statements)
references
References 79 publications
2
147
1
3
Order By: Relevance
“…EML4-ALK is the most common gene fusion in NSCLC patients. Besides, a series of other ALK fusion partners have been discovered in NSCLC, including KIF5B, KLC1, and TPR, and most of these ALK fusions in NSCLC patients respond well to the ALK inhibitor crizotinib[6].In our case, the DNA-based NGS suggested that LOC101927285-ALK rearrangement may form a LOC101927285-ALK fusion protein, which is probably inconsistent with the prediction of DNA breakpoint. But either way the positive Ventana staining and effectiveness of crizotinib indicates that this DNA rearrangement does lead to the activation of ALK fusion protein and drives the initiation of the tumor.…”
contrasting
confidence: 71%
“…EML4-ALK is the most common gene fusion in NSCLC patients. Besides, a series of other ALK fusion partners have been discovered in NSCLC, including KIF5B, KLC1, and TPR, and most of these ALK fusions in NSCLC patients respond well to the ALK inhibitor crizotinib[6].In our case, the DNA-based NGS suggested that LOC101927285-ALK rearrangement may form a LOC101927285-ALK fusion protein, which is probably inconsistent with the prediction of DNA breakpoint. But either way the positive Ventana staining and effectiveness of crizotinib indicates that this DNA rearrangement does lead to the activation of ALK fusion protein and drives the initiation of the tumor.…”
contrasting
confidence: 71%
“…A genetic alteration of the anaplastic lymphoma kinase (ALK) gene is present in 3–5% of NSCLCs. Patients with this gene alteration are most often younger in age, female, and nonsmokers with adenocarcinoma [ 4 , 5 ]. The FDA approved the first ALK inhibitor, crizotinib, for ALK-positive locally advanced or metastatic NSCLC in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In 3–7% of cases, NSCLC is associated with various translocations in the ALK gene, leading to the formation of more than 19 chimeric proteins, including EML4, KIF5B, KLC1, and TPR. However, regardless of the genes involved in the translocation, all chimeric products retain the ALK kinase domain, which is responsible for constitutive oncogenic activation of the ALK signaling pathways (including Ras/Raf/MEK/ERK1/2, JAK/STAT, PI3K/Akt, PLC-γ signaling pathways) that regulate migration, proliferation, and cell survival [ 208 ]. Most chimeric ALKs are susceptible to the inhibitor crizotinib, which has been shown to be highly effective in the treatment of similar forms of NSCLC.…”
Section: Emt and Resistance To Antitumor Therapy: Role In The Formatimentioning
confidence: 99%